Induction of stilbene synthase by Botrytis cinerea in cultured grapevine cells - Liswidowati; Melchior, Frauke; Hohmann, Frank; Schwer, Burkhardt; Kindl, Helmut (Planta, 1991)
The interaction between Botrytis cinerea Pers. and grapevine (Vitis vinifera L.) was studied in a model system of reduced complexity. Cultured plant cells and fragments of fungal cell wall were used to simulate some of the processes taking place upon infection of grapevine with B. cinerea. A soluble glucan elicitor was prepared from the fungal cell wall by acid hydrolysis. Like the insoluble wall preparation, the soluble fragment derived from the cell wall acted upon plant cells in eliciting stilbene formation. In grapevine cells, the interaction with the fungus led to a dramatic shut-off general protein synthesis and to the selective formation of a small set of proteins involved in induced resistance. The proteins synthesized de novo with highest rates were stilbene synthase (StiSy) and l-phenylalanine ammonia-lyase (PAL). Stilbene synthase was purified to apparent homogeneity and its molecular properties were characterized. The enzyme is a homodimer with subunit Mr 43 000 and pl = 5.4. Although there were indications of the presence of isoenzymes, these were not distinguished by charge differences. In size, the grapevine StiSy shows microheterogeneity and differs from the appreciably larger enzyme prepared from peanut. Prior to induction by fungal attack, virtually no stilbenes are formed in the plant cell. Upon induction of the pathway leading to the stilbene resveratrol, StiSy activity determines the ratelimiting step in the metabolic sequence. The highly induced grapevine cells produce and secrete resveratrol and derivatives which are known to be fungistatic.
Gesehen am 06.09.2023